Organocatalytic Asymmetric Synthesis of Indole-Based Chiral Heterocycles: Strategies, Reactions, and Outreach - Zhang, Yu-Chen; Jiang, Fei; Shi, Feng (Accounts of chemical research, 2020)
Conspectus Indole-based chiral heterocycles constitute a class of important heterocyclic compounds that are found in numerous pharmaceuticals, functional materials, and chiral catalysts or ligands. Catalytic asymmetric synthesis, for which the 2001 Nobel Prize in Chemistry was awarded, has been demonstrated to be the most efficient method for accessing chiral compounds. Therefore, the catalytic asymmetric synthesis of indole-based chiral heterocycles has attracted great interest from the scientific community. However, the strategies toward this goal are rather limited, and great challenges remain in this field, such as metal contamination in the products, the limited number of platform molecules with versatile reactivity, and the limited number of catalytic asymmetric reactions that offer high step economy, atom economy, and excellent enantiocontrol. Therefore, novel strategies for the catalytic asymmetric synthesis of indole-based chiral heterocycles are urgently needed. To achieve this goal, our group has developed a series of unique strategies, such as designing and developing versatile platform molecules and their corresponding organocatalytic asymmetric reactions to access indole-based chiral heterocycles. In this Account, we describe our efforts to address the remaining challenges in this research field. Namely, we have designed and developed vinylindoles, indolylmethanols, arylindoles and indole derivatives as versatile platform molecules for the construction of indole-based chiral heterocyclic scaffolds with structural diversity and complexity. Based on the reactivities of these platform molecules, we have designed and accomplished a series of organocatalytic asymmetric cycloaddition, cyclization, addition and dearomatization reactions with a high step economy, atom economy and excellent enantiocontrol. Using these strategies, a wide range of indole-based chiral heterocycles, including five-membered to seven-membered heterocycles, axially chiral heterocycles and tetrasubstituted heterocycles, have been synthesized with high efficiency and excellent enantioselectivity. In addition, we have investigated the properties of some indole-based chiral heterocycles, including their bioactivities and catalytic activities, and showed that these chiral heterocycles have potent anticancer activities and promising catalytic activities in asymmetric catalysis. These results help elucidate the potential applications of indole-based chiral heterocycles in drug development and chiral catalysts. The organocatalytic asymmetric synthesis of indole-based chiral heterocycles has undoubtedly become and will continue to be a hot topic in the field of asymmetric catalysis and synthesis. Our efforts, summarized in this Account, will not only open a window for the future development of innovative strategies toward organocatalytic asymmetric synthesis of indole-based chiral heterocycles but also inspire chemists worldwide to confront the remaining challenges in this field and prompt further advances.